Anthroponyms: Characteristics of Naming Tolaki People in Taenango Oral Literature (Heroic Epics) in Southeast Sulawesi - Basrin Melamba; M. Sabaruddin Sinapoy; Pawenari Hijjang; Muhammad Basir (Pascasarjana ISBI Bandung Conference Series, 2025)
The study aims to identify the characteristics and patterns of self-naming among the Tolaki people as depicted in the Taenango oral literature, a famous epic. The findings reveal three key aspects: first, a distinct classification of names for men and women, consistently appearing in folklore and local history. Second, the use of prepositions or prefixes like La, Le, Ta, To, Wa, We, and others, which differentiate male and female names. Third, names often include titles such as Sangia (God) or Tumonda Hopalea (Pioneer Commander). These naming conventions, rooted in Taenango literature, continue to influence contemporary naming practices among the Tolaki people. Keywords: Pattern; Naming; literature; Taenango; and Tolaki